Plasma-assisted synthesis and high-resolution characterization of anisotropic elemental and bimetallic core–shell magnetic nanoparticles - Hennes, M.; Lotnyk, A.; Mayr, S. G. (Beilstein Journal of Nanotechnology, 2014)
Magnetically anisotropic as well as magnetic core–shell nanoparticles (CS-NPs) with controllable properties are highly desirable in a broad range of applications. With this background, a setup for the synthesis of heterostructured magnetic core–shell nanoparticles, which relies on (optionally pulsed) DC plasma gas condensation has been developed. We demonstrate the synthesis of elemental nickel nanoparticles with highly tunable sizes and shapes and Ni@Cu CS-NPs with an average shell thickness of 10 nm as determined with scanning electron microscopy, high-resolution transmission electron microscopy and energy-dispersive X-ray spectroscopy measurements. An analytical model that relies on classical kinetic gas theory is used to describe the deposition of Cu shell atoms on top of existing Ni cores. Its predictive power and possible implications for the growth of heterostructured NP in gas condensation processes are discussed.
Keywords: bimetallic magnetic nanoparticle; core–shell; magnetron sputtering; plasma gas condensation

(untitled) - Pankhurst, Q. A.; Connoly, J.; Jones, S. K.; Dobson, J. (J. Phys. D: Appl. Phys., 2003)

(untitled) - Ferreira, L.; Karp, J. M.; Nobre, L.; Langer, R. (Cell Stem Cell, 2008)

(untitled) - Duguet, E.; Vasseur, S.; Mornet, S.; Devoisselle, J.-M. (Nanomedicine, 2006)

(untitled) - Alexiou, C.; Arnold, W.; Klein, R. J.; Parak, F. G.; Hulin, P.; Bergemann, C.; Erhardt, W.; Wagenpfeil, S.; Lübbe, A. S. (Cancer Res., 2000)

(untitled) - Ferrando, R.; Jellinek, J.; Johnston, R. L. (Chem. Rev., 2008)

Nanoscale Magnetic Materials, Applications - Liu, J. P.; Fullerton, E.; Gutfleisch, O.; Sellmyer, D. J. (Springer, 2009)

(untitled) - Granqvist, C. G.; Buhrman, R. A. (J. Appl. Phys., 1976)

(untitled) - Hahn, H.; Averback, R. S. (J. Appl. Phys., 1990)

(untitled) - Haberland, H.; Karrais, M.; Mall, M.; Thurner, Y. (J. Vac. Sci. Technol., A, 1992)

(untitled) - Bai, J.; Wang, J.-P. (Appl. Phys. Lett., 2005)

(untitled) - Krishnan, G.; Verheijen, M. A.; ten Brink, G. H.; Palasantzas, G.; Kooi, B. J. (Nanoscale, 2013)

(untitled) - Llamosa Pérez, D.; Espinosa, A.; Martínez, L.; Román, E.; Ballesteros, C.; Mayoral, A.; García-Hernández, M.; Huttel, Y. (J. Phys. Chem. C, 2013)

(untitled) - Hihara, T.; Sumiyama, K. (J. Appl. Phys., 1998)

(untitled) - Yamamuro, S.; Sumiyama, K.; Suzuki, K. (J. Appl. Phys., 1999)

(untitled) - Gracia-Pinilla, M.; Martínez, E.; Silva Vidaurri, G.; Pérez-Tijerina, E. (Nanoscale Res. Lett., 2009)

(untitled) - Quesnel, E.; Pauliac-Vaujour, E.; Muffato, V. (J. Appl. Phys., 2010)

(untitled) - Ayesh, A. I.; Thaker, S.; Qamhieh, N.; Ghamlouche, H. (J. Nanopart. Res., 2011)

(untitled) - Werner, R.; Höche, T.; Mayr, S. G. (CrystEngComm, 2011)

(untitled) - Bray, K. R.; Jiao, C. Q.; DeCerbo, J. N. (J. Appl. Phys., 2013)

(untitled) - Xu, Y.-H.; Wang, J.-P. (Adv. Mater., 2008)

(untitled) - Baletto, F.; Mottet, C.; Ferrando, R. (Phys. Rev. Lett., 2003)

(untitled) - Hennes, M.; Buchwald, J.; Mayr, S. G. (CrystEngComm, 2012)

(untitled) - Wang, Y.; Hou, M. (J. Phys. Chem. C, 2012)

(untitled) - Christensen, A.; Stoltze, P.; Norskov, J. K. (J. Phys.: Condens. Matter, 1995)

(untitled) - Xiao, S.; Hua, W.; Luo, W.; Wu, Y.; Li, X.; Deng, H. (Eur. Phys. J. B, 2006)

(untitled) - an Mey, S. (CALPHAD: Comput. Coupling Phase Diagrams Thermochem., 1992)

(untitled) - Tyson, W. R. (Surf. Sci., 1977)

(untitled) - Bogaerts, A.; van Straaten, M.; Gijbels, R. (J. Appl. Phys., 1995)

(untitled) - Hagena, O. F. (Surf. Sci., 1981)

(untitled) - Qiu, J.-M.; Wang, J.-P. (Appl. Phys. Lett., 2006)

(untitled) - Ganeva, M.; Pipa, A. V.; Hippler, R. (Surf. Coat. Technol., 2012)

(untitled) - Knauer, W. (J. Appl. Phys., 1987)

Diffusion: Mass Transfer in Fluid Systems - Cussler, E. L. (Cambridge University Press, 1997)